Analysis The Influence Of CSR, Cash Flow, And GCG On Dividend Policy In Consumer Goods Sector - Turnip, Jainal Abidin; Usman, Bahtiar (Universitas Wiralodra, 2024)
Investors need information that can support their decision to invest, including analyzing the factors that influence a company's decision to distribute dividends. This research aims to analyze and explain the influence of CSR, cash flow and GCG on dividend policy in consumer goods sector companies listed on the IDX. The independent variables are CSR, cash flow, GCG, leverage, liquidity and company size and the dependent variable is dividend policy. Dividend policy is chosen as the dependent variable because it is used to determine the value of earnings per share to be distributed to shareholders. The data used in this research is secondary data sourced from annual reports of consumer goods sector companies listed on the Indonesia Stock Exchange (BEI) during the 2013-2022. The research sample was selected using a purposive sampling method , which was chosen because it allows for a more in-depth analysis of research subjects with specific characteristics. As a result, 13 companies were obtained as samples. The data analysis used for hypothesis testing is multiple regression analysis using E-Views software. The results show that CSR, cash flow, GCG, and liquidity as control variables have a positive influence on dividend policy. The study also indicates that leverage and firm size as control variables do not affect dividend policy. These findings provide significant implications for management in conducting CSR activities and considering the conditions of cash flow, GCG, and liquidity when determining dividend policy . Based on the results, the Adjusted R-squared value indicates that Corporate Social Responsibility, Good Corporate Governance, Cash Flow, Leverage, Liquidity, and Company Size collectively influence Dividend Policy by 31.33%, while the remaining 68.67% is influenced by factors outside the research model.